Publication Status of Theses among Post-graduate Students in Nursing from Institute of Medicine - Khatri, Pratima; Chapagain, Bigya; Sharma, Mohan Raj (Journal of Nepal Health Research Council, 2024)
Background: Publication of the research work done during the master’s program is highly desirable. However, there is a paucity of data on the number of publications, especially from low-income countries. The objective was to find out the status of the publication of the theses of post-graduate students in Nursing from the Institute of Medicine, Tribhuvan University, Nepal from 2015-2019. Methods: Cross-sectional analytical design with a structured interview via telephone was done for data collection. Independent variables were age, marital status, current work status, current working organization, type of research, year of graduation, and facilitators and barriers to publication, whereas dependent was the publication status of the thesis. Results: Two hundred five (76.2%) out of 269 participated in the study. The age group ranged from 27 to 50 years (mean ± SD = 36.6±4.8). The majority 89.3% were married. Currently working in academic institutions was 51.7%. One hundred ninety-eight (96.6%) respondents performed a cross-sectional descriptive study. Only 2.9% of studies were cross-sectional analytical and 0.5% were qualitative. Seventy-five (36.6%) respondents published their theses. Twenty-seven (36.0%) were published in PubMed-indexed journals. The most common facilitator for publication was academic satisfaction [59 out of 75(78.7%)] followed by encouragement from supervisors 52.0% and peers 40.0%, whereas the commonest barrier to publication was lack of interest [80 out of 124 (64.5%)] followed by lack of confidence 51.6%. Conclusions: Based on the results, more than one-third of the participants published their theses in national and international journals including those indexed in PubMed. Provision of university research grants, development of publication culture among post-graduate students, and making a provision of academic publication before degree awards should be encouraged for more academic publication. Keywords: Journals; Nepal; nursing; publication status; thesis.